STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER DISIPLIN SISWA DI SMK AL-AMANAH KABUPATEN TANGERANG - Dewi Putri Wulan Sari; Eka Naelia Rahmah (Qiro'ah : Jurnal Pendidikan Agama Islam, 2022)
The formation of character through discipline is very important for the future of students as Discipline in students social life.. The purpose of this study was to find out how the strategy of Islamic Religious Education teachers in shaping the character of students' discipline at SMK AlAmanah, Tangerang Regency. This study uses a qualitative approach with qualitative descriptive research, using the methods of observation, interviews, and documentation, and uses data analysis techniques, namely data reduction, data presentation, and verification . The results of this study indicate that the strategy of Islamic religious education teachers at SMK Al-Amanah Tangerang Regency is implemented well, starting from providing examples and habituation to students, socializing regulations and controlling students, giving punishment or sanctions to students who violate school regulations. as a form of warning. Then giving rewards to students who have complied with school rules in the form of praise and encouragement so that students are more enthusiastic in complying with these regulations.